Aplicativo educacional para apoiar o ensino do processo de enfermagem na assistência à mulher, à criança e à família em amamentação - Resende, Fabíola Zanetti (2018)
Introduction: Nursing care to the woman, the child and the family in the breastfeeding process has a multiplicity of factors that may interfere with the initiation, maintenance and duration of breastfeeding. The development of the nursing process or nursing consultation individualizes the care and makes easier to identify the influencing factors, therefore contributing to reduce premature weaning. The nurse may use a variety of nursing diagnoses and specific nursing interventions to solve the observed problem, showing the importance of the procedures that bring nursing statements representative of clinical practice. This study aimed at aligning the benefits of Computer Information Technologies to Teaching-Learning and Development of the nursing process / nursing appointment. Objective: To reorganize the INCP® subset to assist women, children and families in the breastfeeding process, and to develop an application to support the teaching of the nursing process or the nursing consultation to breastfeeding. Methodology: Methodological study. The subset reorganization was performed in five steps: 1) Cross-mapping between the nursing diagnoses and outcomes of the INCP® subset and the 2015 INCP® version; 2) Content Validation of nursing diagnoses and outcomes with judges; 3) Cross-mapping between the nursing interventions of the INCP® subset and the 2015 INCP® version; 4) Validation of nursing interventions with judges; 5) Structuring the INCP® subset to assist women, children and the family in the process of breastfeeding. The application was developed in four steps: 1) Definition of requirements and elaboration of the conceptual map of the application; 2) Generation of alternatives of implementation and prototyping; 3) Tests; and 4) Implementation. Results: 13 diagnoses / outcomes obtained (validation index of content) VIC greater than or equal to 0.8 (13.3%); 34 from 0.6 to 0.79 (34.7%); 51 less than 0.6 (52%). The terms “Lack of privacy”, “Decision making towards effective breastfeeding”, “Effective mother role performance” and “Improved mother role performance” had no other validated statement that maintained the relationship between nursing diagnoses and outcomes, therefore three statements were added, totaling 50 nursing diagnoses/outcomes. Of the 396 nursing interventions submitted for validation, 350 obtained VIC greater than or equal to 0.80. The application “Cuidartech Amamenta” contains five navigation options: “INCP® Breastfeeding Subset”, which brings the diagnoses, outcomes and interventions; “Case studies”, which contains 10 cases for the exercise of diagnostic reasoning; “About INCP®”, “About INCP® Subsets” and “About Interactive Theory of Breastfeeding”, which shows content about each of these topics; and “Credits”, which has information about the purpose of the application and responsible team. Conclusion: The validation process involved nurses from all regions of Brazil, which shows the representativeness of the statements in clinical practice in maternity ward, Neonatal Intensive Care Unit, Human Milk Bank and primary care. The subset, containing 50 diagnoses, 27 outcomes and 350 nursing interventions, served as the basis for the development of the application “Cuidartech Amamenta”. These two tools present themselves as new technologies in nursing that can provide the development of the nursing process or nursing consultation. The application can be used in teaching-learning as a support to students for diagnosis reasoning and decision-making.